2018
DOI: 10.1007/s12020-018-1606-4
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin knockout mice display defective skeletal muscle regeneration and impaired satellite cell self-renewal

Abstract: Although we cannot discern the specific Ghrl-derived peptide responsible for such activities, these data indicate that Ghrl contributes to a proper muscle regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Des-acyl ghrelin fosters muscle regeneration by promoting myoblast differentiation and regeneration [228].…”
Section: Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Des-acyl ghrelin fosters muscle regeneration by promoting myoblast differentiation and regeneration [228].…”
Section: Skeletal Musclementioning
confidence: 99%
“…Both ghrelin and des-acyl ghrelin stimulate proliferating C2C12 skeletal myoblasts [229]. Ghrelin is also important for skeletal muscle cell regeneration following injury, which depends on satellite cells, quiescent precursors that activate, proliferate, and differentiate to repair the damaged tissue [228]. Des-acyl ghrelin reduces skeletal muscle mitochondrial ROS generation [230] and ROS-induced cell injuries by inducing the expression of superoxide dismutase-2 in satellite cells resulting in the induction of the myogenic process and reduction of functional impairment [231].…”
Section: Skeletal Musclementioning
confidence: 99%
“…On the contrary, the finding that old Ghrl KO mice were atrophy-resistant, featuring enhanced physical performance ( Figure 3A , 3B ), lower levels of catabolism-related genes ( Figure 4A – 4C ), and larger myofiber areas than WT mice ( Figure 4E ), was less expected, as we have formerly demonstrated that, upon a traumatic event, muscle regeneration in Ghrl KO mice is reduced, due to an impaired satellite cell self-renewal activity [ 22 ]. Also, old Ghrl KO mice are more susceptible to fasting-induced muscle atrophy likely because of an altered mitochondrial function [ 9 ].…”
Section: Discussionmentioning
confidence: 94%
“…To address whether ghrelin levels during aging affect sarcopenia development, we examined young (3-month-old), adult (6-month-old), middle-aged (12-month-old), and old (24-month-old) Myh6/ Ghrl transgenic mice characterized by high levels of circulating UnAG, up to 100 times more than WT animals (Tg; [ 7 , 13 ]), their WT littermates, and ghrelin knockout ( Ghrl KO; [ 22 ]) mice, lacking all the gene-derived peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation